Investing : the last liberal art - Hagstrom, Robert G., 1956- (Columbia Business School Pub., 2013)
This updated second edition explores basic and fundamental investing concepts in a range of fields outside of economics, including physics, biology, sociology, psychology, philosophy, and literature. It discusses how the theory of evolution disrupts the notion of the efficient market and how reading strategies for literature can be gainfully applied to investing research. Building on Charlie Munger's famous 'latticework of mental models' concept, the book argues that it is impossible to make good investment decisions based solely on a strong knowledge of finance theory alone.